Análise de imagem na avaliação do potencial fisiológico de sementes de soja - Ávila, Maria Alice Bento (2017)
A computerized evaluation of seedlings represents an advance in the optimization of the time used to obtain data regarding the vigor and the reduction of the subjectivity of the analyzes. The objective of this study was to verify the potential of using the element analysis technique by the GroundEye® L 800 equipment in the separation of lots of soybean seeds with different levels of physiological quality and to relate the results of the computerized evaluation with the vigor tests indicated for the culture . For a characterization of the applied lots as water content scores, first count of germination, germination, emergence of seedlings, rate of emergence, accelerated aging and tetrazolium. The image analysis was performed with four - day - old seedlings by the equipment and then analyzed by the software. In the first experiment were studied in cultivars, in the second study six cultivars with four different lots each, in the third experiment two different cultivars with twelve different lots. Using the technique of image analysis in the evaluation of seedlings with four days of germination using the GroundEye® L 800 equipment, it is possible to separate soybean lots of different levels of vigor. There is a relation between the results of the tradicional tests for the evaluation of seed quality and the results obtained in the vigor index obtained in the image analysis.